Flow channelling and variability in transit times and tortuosity in a fractured rock model with small scale heterogeneity - A. Frampton; A. Frampton (Advances in Geosciences)
Transit times and tortuosity for advective particles following water flow in a three-dimensional discrete fracture network with high-resolution representation of internal fracture heterogeneity in aperture is investigated using a numerical model with a stochastic Lagrangian transport framework. The fracture network properties are obtained from field measurements and data of a deep fractured rock formation in the Forsmark site in Sweden. Different assumptions for describing the variance and correlation length used for internal heterogeneity of fracture aperture fields are considered. It is shown that cases with strong variance and correlation length cause earlier first arrivals and delayed late arrivals, thereby extending the range of the transit time breakthrough distribution, compared to the assumption of constant fracture aperture. Also, the timing of peak mass arrival is delayed and its density is reduced. Furthermore, a strong correlation between transit time and tortuosity which occurs for early and bulk mass arrival is revealed, which breaks down for late mass arrival. Thereby two transport regimes are identified, where a first regime is mainly controlled by the network structure and exhibits strong correlation with tortuosity, and a second regime is mainly controlled by the fracture aperture heterogeneity and exhibits weak correlation with tortuosity.